“Life Giving Experience” and Learning Transfer for Educators in Under Resourced Roman Catholic Schools - Peggy Brun; Davin J. Carr-Chellman; Corinne Brion (Adult Education Research Conference, 2022)
This research explored the nature of learning transfer for alumni of the Teacher Formation program (TF), generating findings of significance for adult learning.
Keywords: learning transfer; teacher professional development; spirituality